Terapi Mandi Terhadap Pecandu Narkotika Di Pondok Pesantren Al-Qodir Cangkringan Sleman Yogyakarta - Muslimah Muslimah (Universitas Islam Bunga Bangsa Cirebon, 2020)
This study aims to determine how the process and benefits of bath therapy for narcotic addicts at Al-Qodir Islamic Boarding School, Cangkringan, Sleman Yogyakarta. This research is a qualitative research with two clients who undergo healing due to narcotics addiction. Methods of data collection by interview, observation, documentation. The method of checking the validity of the data used the